Distribution of polyprenol and dolichol in oil palm genotype (Elaeis guineensis) involving lipase activity - TENGKU SITI HABSYAH; Mohammad Basyuni; LUTHFI A.M. SIREGAR; DADANG AFANDI; INDRA SYAHPUTRA (Society for Indonesian Biodiversity, 2021)
Abstract. Habsyah TS, Basyuni M, Siregar LAM, Afandi D, Syahputra I. 2021. Distribution of polyprenol and dolichol in oil palm genotype (Elaeis guineensis) involving lipase activity. Biodiversitas 22: 830-837. The aim of this study was to determine the pattern of chemical compounds from the polyisoprenoid group in oil palm plants that were contributing to the lipase activity. The study was conducted in two locations. A sampling of leaves and fruit mesocarp from 90 progenies was conducted at PT. Socfin Indonesia Aek Loba Plantation, Asahan District, North Sumatra, Indonesia. Biochemical analysis of polyisoprenoid was carried out at the Forest Biotechnology Laboratory, Faculty of Forestry, University of Sumatera Utara, Medan. The results showed that the total lipids in leaves tissue ranged from 0.40 to 1.032 mg/g, with the lowest total lipid found in SL-4966 progeny and the highest total lipid found in SL-9737 progeny. Polyisoprenoid values ??ranged from 1.63 to 10.82 mg/g dry weight. The highest polyisoprenoid content was obtained in SL-10682 progeny, and the lowest was in SL-5045 progeny leaf tissue. The polyisoprenoid ??in fruit mesocarp tissue ranged from 1.79 to 4.14 mg/g. The lowest polyisoprenoid content (1.79 mg/g) of fruit mesocarp was found in SL-4233 progeny, while the highest (4.14 mg/g) was found in SL-5010 progeny.  Dolichol and polyprenol are equally dominant in palm leaves.  Carbon polyprenol chain lengths ranged from C45-C105, and dolichol ranged from C50-C110. The polyprenol carbon chain lengths in the mesocarp tissues were C65-C120 and dolichol was C65-C125. Polyisoprenoid analysis on oil palm leaf and fruit mesocarp tissue showed that lipid patterns of oil palm leaf and mesocarp were categorized as type II lipid patterns. It provides important information for selecting genotypes of low lipase activity of oil palm plants.